THE EFFECTIVENESS OF VIRTUAL REALITY IN REDUCING ANXIETY IN HEMODIALYSIS PATIENTS: NARRATIVE REVIEW - Mesya Mesya; Reni Muhka (Prosiding Seminar Nasional Indonesia, 2025)
Chronic Kidney Disease (CKD) requires regular hemodialysis therapy to replace impaired kidney function. However, this procedure often causes anxiety that impacts psychological well-being and patient compliance with treatment. One of the developing non- pharmacological interventions is Virtual Reality (VR), which is used as a distraction technique to reduce anxiety during hemodialysis. This review aims to evaluate the effectiveness of using VR in reducing anxiety in patients undergoing hemodialysis therapy. This study is a systematic review with a literature search from the Google Scholar, ProQuest, and PubMed databases for the period 2020–2025. The keywords "Virtual Reality," "Anxiety," and "Hemodialysis" were used with Boolean operators to filter the search results. Studies were selected based on the PICOS framework, and their quality was assessed using the Joanna Briggs Institute (JBI). Of the 1,414 studies found (960 from Google Scholar, 129 from ProQuest, and 325 from PubMed), four relevant studies were identified and further analyzed. The review results showed that VR is effective in reducing anxiety in hemodialysis patients. VR serves as a cognitive distraction, relaxation method, and parasympathetic response stimulant that helps reduce stress hormone levels and increase patient comfort during procedures. The implementation of VR has the potential to improve patient comfort, minimize dependence on anti-anxiety medications, and support technological innovation in healthcare. Further research is needed to explore the duration, frequency, and type of VR content that is most effective in reducing anxiety in hemodialysis patients and its impact on other psychological aspects, such as quality of life and adherence to therapy.